2003
DOI: 10.4161/cc.2.6.515
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase as a Growth-Promoting Factor

Abstract: Beyond its role in telomere maintenance, telomerase provides additional functions in tumorogenesis, DNA repair, and cell survival. Telomerase protects cells from apoptosis and necrosis, and stimulates growth in adverse conditions. Furthermore, gross overexpression of the catalytic subunit of telomerase (hTERT) may act as a hyperproliferative signal to induce a senescence-like phenotype in normal fibroblasts, which is similar to the senescence induced by overexpression of oncogenes. As some of these functions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 57 publications
0
26
0
1
Order By: Relevance
“…We believe that in addition to telomere length regulation, telomerase acts as a growth-promoting factor and modulates the expression of various growth-promoting factors (basic fibroblast growth factor and epidermal growth factor receptor; 24,25). In fact, some of our preliminary results indicate that number of growth-promoting factors and cell cycle regulatory components are regulated by hTERT.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We believe that in addition to telomere length regulation, telomerase acts as a growth-promoting factor and modulates the expression of various growth-promoting factors (basic fibroblast growth factor and epidermal growth factor receptor; 24,25). In fact, some of our preliminary results indicate that number of growth-promoting factors and cell cycle regulatory components are regulated by hTERT.…”
Section: Discussionmentioning
confidence: 82%
“…These results suggest that genistein inhibits growth of prostate cancer cells not due to an increase in cell death; rather, genistein is involved in regulating the expression of genes that are involved in cell proliferation. Because telomerase provides indefinite replicative potential of cancer cells and acts as a growthpromoting factor (24,25), we examined whether telomerase activity was repressed by the treatment of genistein in prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of carcinogenesis involves several events that inhibit the senescence response to these traits, such as activation of telomerase that counteracts telomere-mediated replicative senescence, as well as inactivation of tumor suppressors p53 or p16, which mediates a bypass of both STASIS and the M1 stage of replicative senescence. The senescence-promoting and senescence-suppressing factors in tumor cells exist in a dynamic equilibrium, which is perhaps best illustrated by the report that overexpression of hTERT not only inhibits but -at very high levels -also promotes senescence (Gorbunova et al, 2003). Many recent studies have demonstrated that a variety of stimuli can shift this equilibrium in favor of senescence, thereby stopping the growth of tumor cells.…”
Section: Cajoling Tumor Cells Into Senescence: Genetic Approachesmentioning
confidence: 91%
“…Ribosomal biogenesis is a prerequisite for growth and proliferation, and telomerase acts as a growth-promoting factor [20][21][22] . Thus, we investigated whether the inhibition of Pol I transcription by knockdown of TERT influences cellular proliferation and analysed the increase in the number of HCT116 cells stably transfected with the hTERT-specific shRNA or with the DNhTERT construct.…”
Section: Resultsmentioning
confidence: 99%